Analysis Of The Causes Of Cracks In The Cylinder Liner That Cause Non-Optimal Performance Of The Yuchai Yc 6a170c Generator Engine On Board Mv Lagun Mas - Sarifuddin Sarifuddin (Dinasti Research, 2022)
The liner cylinder is an important part of the yuchai yc 6a170c diesel engine which is a tube where the piston works and moves up and down to stimulate air and transfer heat into kinetic power. To obtain optimal engine power, efforts are made not to crack or leak in the liner cylinders of the yuchai yc6a170c generator engine. Factors causing the cracking of the liner cylinder such as the lack of a good cooling system on the liner cylinder so that the liner cylinder experiences a temperature increase caused by friction from the piston so that it can cause cracks. However, this should be reduced by regular maintenance and periodic checks of the pumps and raw materials used in the yuchai yc6a170c liner cylinders on the MV Lagun Mas ship. The method used in this research uses descriptive qualitative researchmethods. The research report will contain excerpts of data to provide an overview of the report presentation, the data comes from interview manuscripts, field notes, photos, personal documents, notes or memos and other official documents. The results of this study show that the importance of carrying out periodic maintenance on oil pumps and seawater pumps so that cooling on the liner cylinders can run optimally.